Study guides

Q: What is 9 plus the square root of 7?

Write your answer...

Submit

Related questions

The square root of 9 is 3, therefore 3 + 7 = 10

(sqrt(9) - sqrt(12) + sqrt(16)) x sqrt(2) = -2 sqrt(6) + 7 sqrt(2)

Square root of 49 = 7... Square root of 9 = 3... 3 x 7 = 21

The answer is 0.

Square root of 9 is 3... (-7) - 3 = -10 ... Answer: -10

Square root of (7 over 9) = 0.8819 (Square root of 7) over 9 = 0.2940 Highlights the importance of brackets, doesn't it?

The square root of 81 is: ±9 (9 or -9)A square root is a number which, when multiplied by itself, equals the original number. As 9 x 9 = 81 and -9 x -9 = 81, the answer is plus or minus nine.

3+14 = 17

sqrt(4) = 2 sqrt(9) = 3 Therefore, the square root of 4 plus the square root of 9 is equal to 2 + 3 = 5.

√567 = √(9*9*7) = √9√9√7 = 9√7

Example: The square root of 54 The square root of 54 is not an integer, since 54 is not a perfect square. The square root of 54 will be between 7 and 8, since 54 is between 49 and 64. Since 54 is closer to 49 than it is to 64, the square root will be closer to 7 than 8. I'd estimate the square root of 54 to be approximately 7.35 The actual square root is plus or minus 7.3484692 To simplify a square root, search for any factors greater than one that are perfect squares. Since 54 = 9 x 6, the square root of 54 equals the square root of 9 x 6 equals the square root of 9 times the square root of 6. The square root of 9 is 3, so the square root of 54 simplified is 3 times the square root of 6.

I would say 19 as the square root of 9 is 3, plus 16, makes 19. I would assume the questioner expects many people to answer 5 which is the square root of the sum of 9 and 16.

the square root of 9 is 3 so 1 +3 = 4

7

if x is equal to the square root of 81 then x is ±9 (plus or minus 9)

The square root of 49 is 77, because, 7 x 7 = 49.

The square root of eight is in between the square root of 7 and the square root of 9, which equals 3.

9

Plus or minus 3i.

Square root of 8 = 2.82842712 It is clear from the value that it doesn't lie between 7 and 9.

Square root(40) = 6.3 6.3 + 9 = 15.3 Unless you mean it this way (square root of 49): Square root(49) = 7.0

1 plus (6 divided by ((square root of 9) plus (square root of 9))) or 9/(9-6)-1=2

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4

9(sqrt 3) + 3(sqrt 3) = 12(sqrt 3)

Square root of one is one, so four times this is four, add 9 is 13